Microstructure and microsegregation of directionally solidified Ti-45Al-8Nb alloy with different solidification rates - Xu, Xiang-Jun; Song, Lin; Jin, Xiao-Ou; Han, Dong-Dong; Wang, Xin; Lin, Jun-Pin (Rare metals, 2016)
Microstructure and microsegregation of directionally solidified Ti-45Al-8Nb alloy were investigated by scanning electron microscopy（SEM）,transmission electron microscopy（TEM） and electron probe microanalyzer（EPMA）.For the alloy solidified at the solidification rates（v） ranging from 10 to 400 μm·s~（-1）,the microstructure of the mushy zone exhibits a cellular-dendritic structure at lower growth rate（v=10-50 μm·s~（-1）） and a typical dendritic morphology at higher growth rate（v = 100-400 μm·s~（-1））.The relationship between primary dendrite arm spacing（λ_1）and v is λ_1=1.08×10~3v~（-0.35）.Al and Nb elements segregate at interdendritic zone and in the dendritic core,respectively.In solid of mushy zone,a relatively flat concentration profile is observed for the typical dendrite structure,and Nb enriches in B2 phase induced by β→α＋βtransformation.The content of B2 phase is hardly affected by v.The extent of microsegregation in steady-state zone decreases at a lower growth rate because holding the samples at higher temperature after solidification for a long time can homogenize the solid effectively.